Mapping worlds: International perspectives on Social and Cultural Geographies - Benach, Núria (Documents d’Anàlisi Geogràfica, 2008)
KITCHIN, Rob (ed.) Mapping worlds: International perspectives on Social and Cultural Geographies Londres; Nueva York: Routledge, 2007; 372 p. ISBN-10: 0415438284